The Intention to Share the Professional Knowledge of University Lecturers: Empirical Evidence from Vietnam - Uong, Lan Ngoc Thi (Journal of Posthumanism, 2025)
The study aims to identify the factors that directly influence lecturers’ intentions to share professional knowledge at universities in Vietnam. A total of 315 survey samples were analyzed using quantitative methods, including reliability testing, exploratory factor analysis, correlation analysis, and binary logistic regression. The results indicate that attitude, reward mechanisms, confidence in knowledge, information technology, subjective norms, and perceived behavioral control directly influence university lecturers’ intentions to share professional knowledge. Based on these research findings, several governance implications are proposed to create policies, design support systems, and foster an environment that encourages knowledge sharing in education, thereby enhancing the effectiveness of training, research, and sustainable development for university lecturers.